Determination of arsenic species in seafood samples using a combination of HPLC and ICP-MS after ultrasonic assisted sample preparation - Sel, Sabriye; Aydogan, Busra; Koyuncu, Ikbal (ELSEVIER, 2026)
In this study, an analytical method was applied for the separation and determination of inorganic and organic arsenic species (As+3, As+5, AsB, MMA) in anchovy, haddock, mussels and prawns using HPLC coupled with ICP-MS. Efficient separation of the arsenic species on the HPLC-ICP-MS system was achieved using 50 mM (NH4)2CO3 at pH 9.50 diluted in 1 % methanol and 0.50 mM EDTA as mobile phase. The arsenic species were extracted from the samples by means of ultrasonically assisted sample preparation. The LOD/LOQ values of the detection system were 0.07/0.22 ng/mL, 0.12/0.41 ng/mL, 0.06/0.22 ng/mL and 0.03/0.11 ng/mL for arsenobetaine (AsB), As+3, methylarsonic acid (MMA) and As+5, respectively. The relative standard deviations calculated for the lowest calibration standards ranged between 1.01 and 7.88 %, verifying good precision for replicate measurements. The accuracy of the method was validated by spike recovery experiments, with recorded recoveries in the range of 85-117 %.The total arsenic content of the extracts was determined by direct ICP-MS analysis. A certificated reference material (NIST-1573A) was analyzed for the total As concentration. The method was successfully applied for the qualitative and quantitative determination of AsB, As+3, MMA and As+5 in the seafood samples ranging from 6.0 to 5700 ng/g. The carcinogenic and non-carcinogenic risk for haddock and anchovies was low, whereas the carcinogenic risk for prawns was relatively high but below the threshold value, according to the risk assessment of the samples.
Keywords: Inorganic As; Organic As; HPLC-ICP-MS; Seafood; SPECIATION ANALYSIS; EXTRACTION; TOXICITY; FOOD; ORGANOARSENICALS; OPTIMIZATION; STABILITY; EXPOSURE; ELEMENTS; WATER; Chemistry